Problematiek van voorgraadse studenteverpleegkundiges se leerervaring in primêre gesondheidsorgklinieke - MacKenzie, Margaret Juliana (University of the Free State, 2010)
The aim of this research was to assess the problems that undergraduate nursing students of the University of the Free State encounter during placement in primary health care (PHC) clinics, which have a negative influence on their learning experience. The need for such research became evident from anecdotal feedback and the fact that primary health care is the core of the existing curriculum. A qualitative, explorative and descriptive research design was used, firstly to examine the problems experienced by the participating triad (PHC nurse practitioners, facilitators of the academic nursing school and the students) during the placement of students in PHC clinics. Secondly, the participating triad were requested to offer suggestions to improve or optimise the learning experience of future students in PHC practice. Data was collected mainly by means of nominal group technique (NGT) interviews and documentary analysis. Diverse problems and suggestions were offered. The same five categories were identified in the data of all groups, namely learning environment, professional socialisation, learning opportunities, culture sensitivity and management. However, the priority sequence of the categories as determined by the participating triad differed. The above sequence (from the highest to the lowest) was for the “problems”, but for the “suggestions” it was learning opportunities, learning environment, culture sensitivity, professional socialisation and management. The identified main problems were, among others, lack of support and ineffective communication. Lack of support is closely associated with negative attitudes and inadequate knowledge. Communication among institutions, within institutions and among colleagues must improve. Recommendations were aimed at improving communication with and supporting various role players. Not only must the students be supported, but those who guide them in the practice setting. The training of nursing students must take place within a partnership in which all the partners play an equally important role and discharge their responsibilities with insight and accountability.
Keywords: Nurses -- Study and teaching (Higher); Nursing students -- Training of; Community health nursing -- South Africa; Communication; Support; Culture sensitivity; Primary health care clinics; Clinical placements; Clinical learning environment; Clinical learning opportunity; Clinical experience; Dissertation (M.Soc.Sc. (Nursing))--University of the Free State, 2010